RESILIENSI: KUNCI SUKSES FULL-TIME MOM - Kirana, Liuciana Handoyo; Fransisca Iriani Roesmala Dewi; Riana Sahrani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The role of a mother has a big influence in creating family happiness and prosperity. Most highly educated women are willing to leave office jobs and decide to become full-time mothers. However, as time went by, this full-time moms experienced parental burnout because of the new routine. Parental burnout is a fatigue syndrome caused by excessive chronic stress in carrying out one's role. This is caused by household work and childcare that are never completed in everyday life. As a result, full-time moms will feel physically and psychologically bored and exhausted. Resilience is resilience in facing challenges. Full-time moms who have resilience will be able to face parental burnout and achieve family well-being. Family well-being includes emotional and physical well-being within a family. The intervention in the form of a psychoeducational webinar with the theme